Case report: Endoscopic Hemoclip treatment for massive hematemesis caused by a Dieulafoy’s lesion on duodenal papilla caused acute pancreatitis - He, Zhi-wei; Xu, Hui; Shi, Hua; Wang, Yang-mei; Zhong, Han; Liu, Xiao-cong (Frontiers in Medicine, 2023)
Background Dieulafoy’s lesion is an uncommon cause for hemorrhage of digestive tract. It often present with urgent and massive bleeding usually leading to shock, even death. Dieulafoy’s lesions have been reported throughout the digestive tract, but which occurred on duodenal papilla were particular rare and presented challenges in the choice of hemostasis. Case Presentation A 66-year-old male with melena for 2 days was admitted. Gastrointestinal endoscopy revealed blood clots covering the duodenal papilla with oozing blood. During the procedure of trying to place a plastic stent into the duodenal papilla first, the hemorrhage began to present a pulsating bleeding. The patient went into shock. With consent, 2 titanium clips were inserted to clamp the bleeding site to stop the bleeding. The patient complained of epigastric pain 14 hours after the endoscopy. Abdominal CT scan showed signs of acute pancreatitis. Endoscopy was performed to remove the titanium clips, and showed a vessel stump on the duodenal papilla. The patient was discharged from the hospital on the 14th day and followed for 6 mo with no recurrence. Conclusion This case was diagnosed with a Dieulafoy’s lesion on the duodenal papilla which has rarely been reported. Hematemesis was stopped by clamping the vessel stump with titanium clips, but caused an acute pancreatitis. Reviewing the treatment, electrocoagulation might be a better choice, and life support treatment, including central vena catheterization and adequate supply of blood products, should be prepared in advance to provide extra time for the stent placement or vascular intervention treatment.